Revisiting the droplet simulation approach to derive force-field parameters for water on molybdenum disulfide from wetting angle measurements - Leroy, Frédéric (The Journal of chemical physics, 2016)
Owing to its peculiar electronic properties, molybdenum disulfide (MoS2) has been the subject of a growing number of studies in the recent years. In applications, this material and other transition metal dichalcogenides (TMDs) may have to interact with a liquid or polymer phase as well as solutions of biomolecules. It is therefore of primary importance to understand the wetting and adhesion properties of TMDs. Starting from existing models, we derive Lennard-Jones parameters for the interaction between water and the basal plane of MoS2 that are consistent with recent wetting experiments. Molecular dynamics simulations indicate that a stack of only two MoS2 monolayers is necessary to capture the wetting behavior of bulk MoS2. It is found that the Coulomb interaction between water and monolayer and bilayer MoS2 plays no role in the related interfacial thermodynamics. Calculations with the optimized parameters show that the depth of the well of the interaction potential between water and bulk MoS2 is of the order of 8.2 kJ/mol. Such a value is comparable with what was found for graphite and consistent with the fact that the wetting angles of water on graphite and MoS2 are almost equal. The derivation of the force-field parameters is performed using a methodology which, contrary to previous studies, makes a consistent use of droplet calculations. The results of our work should find application in further simulation studies on the wetting behavior of TMDs and other dispersive materials.